Land cover classification based on SAR and optical images using ensemble machine learning - Tian, Gege (Nanyang Technological University, 2022)
Land cover classification is an important remote sensing application. Satellite optical and radar images are two of the most widely used remote sensing images with respective advantages and disadvantages. Using both radar and optical images and machine learning, this project is to explore automatic land cover classification traditionally done manually or semi-manually.